Platforms everywhere : transforming organizations by integrating ecosystems in business design - Rava, Nenad (Emerald Publishing Limited, 2021)
In the 21st century, business innovation faces multifaceted and interdependent challenges that require new concepts, models and tools to drive social and economic transformation. Platforms Everywhere: Transforming Organizations by Integrating Ecosystems in Business Design presents a new comprehensive paradigm for platform businesses and a practical methodology for platforming organizations across sectors and industries. This methodology includes Guiding Principles for Platforming, Platforming Design Steps (with practical tools and methods), and Platforming Navigator. The book explores the Meta platform business model, with four core elements that apply to all platforms regardless of their purpose and focus, and the variety of emerging types of platforms, including hybrid platforms. Featuring strategic guidance for leveraging platform policy, platform governance, and systemic design as key drivers of innovation success, Platforms Everywhere is an essential guide for anyone seeking to understand the challenges and opportunities of cutting-edge business design and organizational transformation. It is particularly beneficial for individuals and organizations interested in business innovation that taps into sources of value in ecosystems to empower stakeholders for learning and collective impact.